Enhanced energy storage properties of La3+ modified 0.92Bi0.5Na0.5TiO3 -0.06Ba(Zr0.2Ti0.8)O3-0.02NaNbO3 ternary ceramic system. (16th April 2021) - Ali Khan, Aqib; Arbab, Safeer Ahmad; Manan, Abdul; Saboor, Abdul; Ullah, Atta; Khattak, Noor Saeed; Ahmad, Iftikhar; Naeem Khan, Muhammad; Bashir, Tariq; Asif, Muhammad; Sadiq, Muhammad; Arif, Muhammad
Abstract: The development in field of hybrid vehicles, telecommunication and energy sectors require dielectric materials having high-energy storage density with optimum thermal stability to operate in certain environment. To fulfil such requirement a new set of materials along the ternary solid solutions of 0.92Bi0.5(1-x) -La(x) Na0.5 TiO3 -0.06Ba(Zr0.2 Ti0.8 )O3 -0.02NaNbO3 (NB1-x Lx T-BZT-NN) (x = 0, 0.03, 0.05, 0.07) were fabricated through solid-state mix oxide route. The XRD patterns analysis confirmed a structural phase transformation from rhombohedral to the tetragonal-P4bm phase when x content increased from 0 to 0.07. The SEM study revealed, dense microstructure for all ceramics accompanied by a decrease in the average grain from 1.66 μ m to 1.05 μ m leading to high densities for these materials with an increase in the x content. The dielectric breakdown field increased from ∼115 to 137 kV cm −1 resulting in an increase in recoverable energy density from ∼0.68 to 1.14 J cm −3 with the increase in x content. Furthermore, excellent temperature stability (±15%) in dielectric permittivity was observed in a wide temperature range for each ceramic. In the present study, a recoverable energy density of 1.14 J cm −3 along with an efficiency of 70.6% was obtained for the composition of x = 0.07.